USE OF NASAL DECONGESTANTS TO CORRECT THE RESPIRATORY AND OLFACTORY FUNCTIONS OF THE NOSE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
As you know, the nose performs several important functions, among which a special place is occupied by the respiratory and olfactory. Nasal breathing is absolutely physiological, unlike breathing through the mouth. This process is carried out by resisting the intra-nasal structures (nasal valve, nasal concha) to the air flow, which createsется отрицательное давлa negative pressure in the chest, which directsair from the nasal cavity and paranasal sinuses to the underlying respiratory tract. On exhalation, when the pressure inthe chest is equalized,the remaining air from the respiratory tract is directed to the nasal cavity and paranasal sinuses [1].